Cartera de crédito de la empresa control automatización y telecomunicaciones del Ecuador - Coautelecom S.A., durante el periodo 2021. - García Valencia, Carmen Jeaneth (2022)
The company "Controles, Automatización y Telecomunicaciones del Ecuador Coautelecom S.A" with RUC 09931270051001 carries out various activities, especially the development and execution of projects in various fields such as electrical and electronic engineering, mining engineering, chemical engineering, among others. It is a legal entity with more than 3 years of experience in the market, very prominent and famous in the city of Guayaquil, thanks to the excellent quality of work it offers its services in cities at the state and national level and also for companies. The credit evaluation requires a detailed procedure to demonstrate the creditworthiness of the client and ensure the recovery of the property. The main objective of this study was to carry out an analysis of the impact of crime on the profits of the Ecuadorian company Control, Automation and Telecommunications Coautelecom S.A., in the Province of Guayas - State of Guayaquil - for the period 2021. Financial management. The methodology will change to qualitative and quantitative methods as we collect and analyze data; The technique used is a survey to collect the criteria and data that allow knowing the crime in relation to its profitability. In the 2021 period, the entity's clients began to default on their payments, which led Coautelecom SA to begin increasing its accounts receivable. Having a high rate of defaults related to collection, due to the lack of manuals that ensure the correct internal processes, as well as the misuse of collection processes to ensure that pending funds are managed efficiently. To justify the credits, the company issues an invoice for its services, which is registered in the accounting system.